50 strategies for teaching English language learners - Herrell, Adrienne L.; Jordan, Michael, 1944- (2020)
This sixth edition of 50 Strategies for Teaching English Language Learners presents a major focus in identifying and teaching students at their language development level. With adoption of the Common Core State Standards (CCSS), educators across the United States are reflecting on exemplary practices and research in strategies for supporting intellectual and educational growth in students of all ages. Common Core does, however, present additional challenges for students who are in the process of acquiring English"--
Predictable routines and signals: reducing anxiety -- Total physical response and total physical response storytelling (TPR and TPRS): integrating movement into language acquisition -- Modeled talk: demonstrating as you talk -- Visual scaffolding: providing language support through visual images -- Realia strategies: connecting language acquisition to the real world -- Vocabulary role-play: building vocabulary through dramatization -- Collecting and processing words: making vocabulary your own -- Manipulatives strategies: using objects to connect concepts -- Choosing technology based on student needs: advancing progress in English language and content learning -- Moving into reading: using multiple strategies to foster comprehension -- Close reading: engaging with text to improve reading comprehension -- Repeated reading: using script writing and reader's theater -- Scaffolding English writing: matching instruction to language development -- Reporting back: verbal practice in curriculum connections -- Leveled questions: adjusting questioning strategies to the language levels of students -- Bilingual books and labels: supporting biliteracy awareness -- Sorting activities: organizing information into categories -- Cloze: using context to create meaning -- Verb action: teaching irregular verbs through experience -- Syntax surgery: visually manipulating English grammar -- Checking for understanding: using questioning strategies to differentiate instruction -- Learning centers: extending learning through hands-on practice -- Communication games: creating opportunities for verbal interaction -- Cognate strategies: using the home language to support English acquisition -- RTI for English language learners: documenting and monitoring student progress and the effectiveness of intervention -- Preview/review: building vocabulary and concepts to support understanding -- Story reenactment: making stories come to life! -- Repetition and innovation: exploring a book to deepen comprehension -- Language focus lessons: supporting English vocabulary and structure acquisition -- Graphic organizers: visually representing ideas, text, and connections -- Advance organizers: getting the mind in gear for instruction -- Guided reading: providing individual support within a group setting -- Cohesion links: understanding the glue that holds paragraphs together -- Language framework planning: supporting academic language and content acquisition -- Free voluntary reading: nothing helps reading like reading -- Culture studies: learning research skills and valuing home cultures in one project -- Microselection: finding key words and main ideas -- Read, pair, share: working with a partner to negotiate meaning -- Attribute charting: organizing information to support understanding -- Integrated curriculum projects: using authentic projects to integrate content knowledge -- KWL and data charts: researching and organizing information -- Collaborative reading: what to do when they can¿t read the textbook -- Cooperative learning: group interactions to accomplish goals -- Learning strategy instruction: acquiring self-help skills -- Multiple intelligences strategies: teaching and testing to student-preferred learning modes -- Multimedia presentations: oral reports for the new millennium -- Small groups and partners: interactions to enhance instruction -- Gist: exploring tough text -- Tutorials: closing the achievement gap -- Combining and scheduling strategies: supporting learning through differentiation.
Includes bibliographical references and index.
Keywords: English language -- Study and teaching -- Foreign speakers; English language -- Study and teaching -- Foreign speakers